Dielectric properties of CaCu3Ti4-xMn xO12 ceramics - W. Makcharoen (2018)
This paper reports the dielectric properties of the Mn doped Cacu3Ti4O12(CCTO) ceramics synthesized by the conventional solid-state reaction method. By partial Mn for Ti substitution, the dielectric loss was suppressed significantly while the dielectric constant (εr) still remained high. The compound CaCu3Ti3.76Mn0.24O12 exhibits a high εr(>1200) and a low dielectric loss (<0.06 at room temperature). Furthermore, the εrvalue of this material is reasonably independent of temperature. SEM micrographs show no impurity in the Mn doped CCTO ceramics, which exhibit dense microstructures without abnormal grains. This Cacu3Ti4O12system appears to be a promising candidate for capacitor applications. © 2009 Amrican Institute of Physics.